BENTUK-BENTUK KEKERASAN YANG DIALAMI PEREMPUAN - Umin Kango (JURNAL LEGALITAS, 2009)
This article aim to know and comprehends form of hardness to woman who often happened. There is four form of hardness to a real woman signifikan vhich often happened in everyday life. Firstly, form of hardness in family. Second, form of hardness in engage/in sexual play. Third, form of hardness in space public. Fourth, form of hardness done by state.